Alexander Nikolaevich Vedensky – the «good genius» of Russian phlebology (to the 90th anniversary of the birthday) - Yu. L. Shevchenko; Yu. M. Stoyko; S. I. Trikhina; E. K. Mazayshvili; V. N. Pavlov; I. O. Sayunov (Вестник хирургии имени И.И. Грекова)
A. N. Vedensky was born on December 6, 1931 in a family of employees. Relatives and family members of A.N. Vedensky, by their merits to the motherland had a significant impact on his development as a doctor and teacher. He excellently graduated from the paramedic school in Bobruisk and the First Medical Institute of Leningrad named after Academician I. P. Pavlov. After graduation, the Institute sent him to Velikiye Luki, Pskov region, where he worked in regional and city hospitals, at an ambulance substation. In 1960, he entered and went to study at the postgraduate course of the Institute of Blood Transfusion (LPIK) in Leningrad.